2016
DOI: 10.1371/journal.pone.0152906
|View full text |Cite
|
Sign up to set email alerts
|

HIV Prevalence and Risks Associated with HIV Infection among Transgender Individuals in Cambodia

Abstract: IntroductionRecognizing transgender individuals have a high risk of HIV acquisition, and to inform policies and programming, we conducted an HIV prevalence and risk behaviors survey among transgender individuals in Cambodia.MethodsCross-sectional survey using a respondent driven sampling method with self-administered audio-computer assisted interviews. HIV testing was performed prior to the questionnaire with results available immediately after. Eligible participants were ≥18 years, identified as male at birth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
42
2

Year Published

2017
2017
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(50 citation statements)
references
References 20 publications
(22 reference statements)
6
42
2
Order By: Relevance
“…The HIV prevalence found in our study is slightly higher than the 4.2% found by a recent study by Weissman et al [17], but both are significantly higher than an earlier study conducted in 2010 which found a prevalence of 2.6% among transgender women [18]. However, direct comparison of findings from this study with those in the previous ones is difficult because of the differences in characteristics of the samples and measures.…”
Section: Discussioncontrasting
confidence: 91%
“…The HIV prevalence found in our study is slightly higher than the 4.2% found by a recent study by Weissman et al [17], but both are significantly higher than an earlier study conducted in 2010 which found a prevalence of 2.6% among transgender women [18]. However, direct comparison of findings from this study with those in the previous ones is difficult because of the differences in characteristics of the samples and measures.…”
Section: Discussioncontrasting
confidence: 91%
“…20 Substance use before or during sex was previously shown to be an independent predictor of condomless receptive anal sex in transwomen. 21,22 …”
Section: Discussionmentioning
confidence: 99%
“…As a result, their unique needs were not reflected in HIV programmes’ goals. 22 There was also a lack of transgender women-specific data to quantify the number reached by outreach programmes and services. In 2012, the first Integrated Biological and Behavioral Survey (IBBS) that specifically included transgender women in Cambodia found an HIV prevalence of 4.2% among this population, 22 which was six times higher than the 0.7% prevalence among the general adult population aged 15–45 years, 23 and about twice higher than the 2.1% among MSM.…”
Section: Introductionmentioning
confidence: 99%
“… 22 There was also a lack of transgender women-specific data to quantify the number reached by outreach programmes and services. In 2012, the first Integrated Biological and Behavioral Survey (IBBS) that specifically included transgender women in Cambodia found an HIV prevalence of 4.2% among this population, 22 which was six times higher than the 0.7% prevalence among the general adult population aged 15–45 years, 23 and about twice higher than the 2.1% among MSM. 24 This 2012 study also found that older age (>35 years), residing in Siem Reap province (a major tourist site), having sex during or after drug use, not using a condom during the last anal sex and low self-esteem were associated with HIV infection among transgender women.…”
Section: Introductionmentioning
confidence: 99%